Genetic Differentiation of Glossina pallidipes Tsetse Flies in Southern Kenya - Okeyo, Winnie A.; Saarman, Norah P.; Bateta, Rosemary; Dion, Kirstin; Mengual, Michael; Mireji, Paul O.; Ouma, Collins; Okoth, Sylvance; Murilla, Grace; Aksoy, Serap; Caccone, Adalgisa (The American journal of tropical medicine and hygiene, 2018)
The tsetse fly Glossina pallidipes , the major vector of the parasite that causes animal African trypanosomiasis in Kenya, has been subject to intense control measures with only limited success. The G. pallidipes population dynamics and dispersal patterns that underlie limited success in vector control campaigns remain unresolved, and knowledge on genetic connectivity can provide insights, and thereby improve control and monitoring efforts. We therefore investigated the population structure and estimated migration and demographic parameters in G. pallidipes using genotypic data from 11 microsatellite loci scored in 250 tsetse flies collected from eight localities in Kenya. Clustering analysis identified two genetically distinct eastern and western clusters (mean between-cluster F ST = 0.202) separated by the Great Rift Valley. We also found evidence of admixture and migration between the eastern and western clusters, isolation by distance, and a widespread signal of inbreeding. We detected differences in population dynamics and dispersal patterns between the western and eastern clusters. These included lower genetic diversity (allelic richness; 7.48 versus 10.99), higher relatedness (percent related individuals; 21.4% versus 9.1%), and greater genetic differentiation (mean within-cluster F ST ; 0.183 versus 0.018) in the western than the eastern cluster. Findings are consistent with the presence of smaller, less well-connected populations in Western relative to eastern Kenya. These data suggest that recent anthropogenic influences such as land use changes and vector control programs have influenced population dynamics in G. pallidipes in Kenya, and that vector control efforts should include some region-specific strategies to effectively control this disease vector.